Statistical Studies of Problems of the Development of Professional-Technical Education in Ukraine - Lesnikova М. V. (Statistics of Ukraine, 2017)
The national system for workforce training in professional-technical education institutions (PTEI) fulfill less than the third part of its key tasks: supply of the domestic economy with the skilled staff in conformity with the labor market needs, balancing of demand and supply of the workforce with due consideration to priority areas of the economic development. The main source of data on the labor market is statistical information collected by the State Employment Service. According to experts, the State Employment Service does not adequately provide the real picture across the labor market, because it administers mostly vacancies with low salary rates or ones not demanding high professional qualifications. Considering the above said, modernization of the education statistics on professional-technical education (PTE) is greatly important as a means for regulating interactions between the market of education services and the labor market. As of 01.01.2017, the PTEI network covered 810 education institutions (not including PTEI in Donetsk and Luhansk regions, located in the antiterrorist operation area), with quite even distribution of PTE institutions across the regions. Drawbacks of the professional education system, not properly adapted to future needs of the domestic economy, resulted in low competitiveness of most part of the youth at the labor market due to lack of professional competencies or lack of the required qualifications and skills. The scopes and professional and qualifications structures of professional training in PTE I are, by large, do not correspond with the employers’ needs. The main indicator reflecting the correspondence of the scopes and the professional and qualifications structure of PTEI graduates to the needs of domestic labor market is the integral coefficient of balance between demand and supply of the workforce trained in PTEI. The key components in the new model for statistical reporting on PTE are as follows: setting the conformity between the nomenclature of definitions (terms) for statistical reporting forms on PTE with definitions (terms) adopted in the Law of Ukraine “On Education”; inclusion of the indicator on PTE costs, by profession (or groups of professions) and source of financing; inclusion of the indicators reflecting the observance of PTE standards for persons with special needs, considering their individual mental, intellectual, physical and sensor abilities. The essential mechanisms for solutions of problems related with PTE development in Ukraine involve building up the institutional framework to implement the new innovative model for regulation of professional training by the principle of public-private-government partnership, i. e. engaging all the resources available with stakeholders and their as more extensive as possible adaptation of foreign (international) approaches and analogues that have proved their durable effectiveness.